2013
DOI: 10.1002/anie.201305980
|View full text |Cite
|
Sign up to set email alerts
|

Nanoplasmonic Imaging of Latent Fingerprints and Identification of Cocaine

Abstract: Search for traces: Aptamer-bound Au nanoparticles (Au NPs) were used to provide high-resolution dark-field microscopy images of latent fingerprints (LFPs) with level 2 and level 3 details. Furthermore, the cocaine-induced aggregation of Au NPs results in a true green-to-red color change of the scattered light, providing a quasi-quantative method to identify cocaine loadings in LFPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
126
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(126 citation statements)
references
References 61 publications
0
126
0
Order By: Relevance
“…Furthermore, the LSPR of metallic nanoparticles neither blinks nor bleaches, demonstrating superiority over conventional fluorophores for long-term monitoring applications. Owing to such outstanding optical properties, metal nanostructures, particularly gold and silver, have become widely used as brightly coloured spatial labels in biological imaging [10][11][12][13][14][15][16], and largely replaced previous methods of fluorescence, chemiluminescence, and radioactive labelling. In addition to being used as labels, the use of plasmonic metal nanoparticles as transducers has been extensively explored in order to translate molecular binding information into changes in extinction or scattering spectra for molecular detection.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the LSPR of metallic nanoparticles neither blinks nor bleaches, demonstrating superiority over conventional fluorophores for long-term monitoring applications. Owing to such outstanding optical properties, metal nanostructures, particularly gold and silver, have become widely used as brightly coloured spatial labels in biological imaging [10][11][12][13][14][15][16], and largely replaced previous methods of fluorescence, chemiluminescence, and radioactive labelling. In addition to being used as labels, the use of plasmonic metal nanoparticles as transducers has been extensively explored in order to translate molecular binding information into changes in extinction or scattering spectra for molecular detection.…”
Section: Introductionmentioning
confidence: 99%
“…90% of the calculated λ max was in the range of 550 ± 5 nm, suggesting the Au NPs were monodispersed. Next, we used a dark-field microscope (DFM) combined with plasmonic resonance Rayleigh scattering (PRRS) spectroscopy 28 to quantitate RDX residues in LFPs. Previous work suggested that NADH acts as a sufficient reducing agent for RDX in enzymatic remediation and detoxification of groundwater containing nitroaromatic pollutants.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Meanwhile, we designed a nanoplasmonic assay to provide quantitative information on RDX explosive residues in LFPs by exploring the competitive reduction of Cu 2+ and RDX by NADH. In addition to the optical advantages of nanoplasmonic imaging of LFPs, 28 the nanoplasmonic detection of RDX residues in LFPs possesses several superiorities. First, the proposed method used an objective lens of different magnifications (4× and 60×) to obtain LFPs images and RDX loadings, respectively.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…When incubated with the fingerprint, the fluorophore-tagged aptamers folded into specific 3D structures and subsequently bound to lysozymes. Recently, Li et al [74] proposed a nanoplasmonic method by employing aptamer-bound AuNPs to visualize LFPs and detect contact residues of cocaine. Because the localized SPR of AuNPs is highly dependent on the interparticle distance, the cocaine-induced aggregation of aptamer-bound AuNPs led to a true green-to-red color change of the scatter- ing in the dark-field image, thus providing the molecular recognition of cocaine loaded into the LFPs.…”
Section: Aptamer-based Reagentsmentioning
confidence: 99%